Proton transfer in hydrogen-bonded degenerate systems of water and ammonia in metal–organic frameworks. Issue 1 (11th December 2018) - Lim, Dae-Woon; Sadakiyo, Masaaki; Kitagawa, Hiroshi
Abstract : Porous crystalline metal–organic frameworks (MOFs) are emerging as a new class of proton conductors through the hydrogen-bonded degenerate system. Abstract : Porous crystalline metal–organic frameworks (MOFs) or porous coordination polymers (PCPs) are emerging as a new class of proton conductors with numerous investigations. Some of the MOFs exhibit an excellent proton-conducting performance (higher than 10 −2 S cm −1 ) originating from the interesting hydrogen(H)-bonding networks with guest molecules, where the conducting medium plays a crucial role. In the overwhelming majority of MOFs, the conducting medium is H2 O because of its degenerate conjugate acid–base system (H3O + + H2 O ⇔ H2 O + H3 O + or OH − + H2 O ⇔ H2 O + OH − ) and the efficient H-bonding ability through two proton donor and two acceptor sites with a tetrahedral geometry. Considering the systematic molecular similarity to water, ammonia (NH3 ; NH4 + + NH3 ⇔ NH3 + NH4 + ) is promising as the next proton-conducting medium. In addition, there are few reports on NH3 -mediated proton conductivity in MOFs. In this perspective, we provide overviews of the degenerate water (hydronium or hydroxide)- or ammonia (ammonium)-mediated proton conduction system, the design strategies for proton-conductive MOFs, and the conduction mechanisms.